2020
DOI: 10.1177/0253717620946439
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of COVID-19 on Mental Health: A Scoping Review of the Existing Scales

Abstract: Background: The coronavirus disease (COVID-19) pandemic, associated with the economic consequences of non-pharmaceutical interventions such as lockdown, has led to mental health consequences among people worldwide. Protecting the mental well-being of populations is an imperative component of fighting the COVID-19 pandemic. This scoping review attempts to present an overview of the existing tools to measure COVID-19-related mental health problems. Methods: Literature search was conducted in the PubMed electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 65 publications
3
41
0
2
Order By: Relevance
“…Numerous psychometric scales have been developed to assess mental health in this period to understand the psychological burden posed by COVID-19 on different populations worldwide. For instance, a scoping review published in 2020 indicated 15 scales measuring COVID-19-associated mental health problems validated among diverse populations across the world [ 35 ]. Specifically, on indicators related to mental health in dental staff [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], six studies have evaluated stress [ 14 , 15 , 18 , 19 , 22 , 23 ] by using different psychometric scales and instruments, including the Depression, Anxiety, and Stress Scale-21 (DASS-21) [ 15 , 19 ], the Kessler’s Psychological Distress Scale K6 [ 18 ], GP-CORE [ 23 ], and open-ended questions about stress-related factors [ 14 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous psychometric scales have been developed to assess mental health in this period to understand the psychological burden posed by COVID-19 on different populations worldwide. For instance, a scoping review published in 2020 indicated 15 scales measuring COVID-19-associated mental health problems validated among diverse populations across the world [ 35 ]. Specifically, on indicators related to mental health in dental staff [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], six studies have evaluated stress [ 14 , 15 , 18 , 19 , 22 , 23 ] by using different psychometric scales and instruments, including the Depression, Anxiety, and Stress Scale-21 (DASS-21) [ 15 , 19 ], the Kessler’s Psychological Distress Scale K6 [ 18 ], GP-CORE [ 23 ], and open-ended questions about stress-related factors [ 14 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As most studies in this review were cross-sectional in nature, future studies should adopt longitudinal designs that may explore how the magnitude and correlators of sleep disorders evolve One of the notable findings of this review was the use of multiple scales for assessing sleep disorders as well as associated mental health problems. Many scholars have adopted previous scales, where is several new scales were introduced during this pandemic 90 . It is essential to conduct extensive factor analysis evaluating the appropriateness of multiple skills so that future research can be conducted using standardized scales and measurements.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…These scales allow a rapid detection of COVID-related stress symptoms, facilitating more efficient resource allocation of public mental health support by prioritizing assistance to the most affected population groups. Some of these questionnaires are the Fear of COVID-19 Scale (FCV-19S) [ 17 ], the Coronavirus Anxiety Scale (CAS, Lee, 2020) [ 18 ], the COVID-19 Phobia Scale (C19 P-S [ 19 ], and the COVID-19 Peritraumatic Distress Index (CPDI [ 9 ], see [ 20 ] for a review. Within these tools, the CPDI probably captures the COVID-related psychological distress most comprehensively, as it incorporates symptoms of a broad array of mental health syndromes and pathologies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%